Polygraph testing in the workplace in South Africa : with reflections on the international labour organization standards, United States of America and Federal Republic of Germany - Scheithauer, Anne (Department of Commercial Law, 2024)
[page 189 missing] This thesis deals with polygraph testing in the South African workplace, which is used in the hiring, disciplining and dismissing of workers. Since the mid-1990s, South Africa's industry has experienced extensive use of polygraph testing, and the trend continues to grow. Polygraph test results are accepted as evidence in labour disputes. The law also permits polygraph testing in some parts of the public sector. This study analyzes the theoretical and scientific basis of polygraph testing in the employment context. It then investigates the legitimacy of such testing in terms of international labour law, before dealing with the United States of America and German jurisdictions, which have different approaches to protection from polygraph testing. Finally, it considers the main focus of the study, South Africa's law of evidence, labour legislation and case law. The thesis argues that polygraph testing does not have a sound theoretical and empirical foundation, in particular when used in the employment context. In South Africa, many unqualified examiners carry out the tests and a supervising statutory body does not exist. Therefore, it is submitted that employers should not use polygraph testing, nor should the results be admissible evidence in labour disputes. Further, existing international labour standards do not support the use of polygraph testing in employment. In particular, it can amount to unfair discrimination. Failing a test or simple refusal to submit to one does not constitute a fair reason for dismissal for misconduct. The ILO states explicitly that polygraph testing should not be used under any circumstances. The United States of America experienced a similar situation in the 1980s, with about two million tests administered on employees every year. That finally led to the enactment of the Employee Polygraph Protection Act of 1988 to regulate the use of polygraph testing in the private sector. Civil and criminal courts are generally reluctant to admit polygraph test results. On the other hand, Germany has always demonstrated a general rejection of polygraph testing, and there is no known use in employment. In Germany, the constitutional rights of employees have priority over the employer's interests in protecting its business. The experiences of both countries could be helpful in finding solutions to South African problems. In South Africa, polygraph testing is extensively applied in private employment but its use is not at all regulated. Currently, an employer can require its employees to undergo testing at any time for any purpose. Employees are disciplined and/or dismissed because they fail an examination or simply refuse to take one, while job applicants are not employed. It is submitted that polygraph testing constitutes a form of psychological testing in terms of section 8 of the Employment Equity Act, and that legislation must be amended to ensure better employee protection.